The Influence of Intrinsic and Extrinsic Rewards on Middle School Teachers’ Job Satisfaction - Ansori Ansori; Iwan Aprianto; Muhammad Yusup; Kholid Ansori; Marzani Marzani (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to determine the effect of intrinsic and extrinsic rewards on teacher job satisfaction at a junior high school in Batanghari. This research is a quantitative study. The population of this study is the number of all teachers who teach at that school, with a sample of 32 teachers. The analysis used is multiple regression analysis, and the data is processed with the help of the SPSS version program 20.0. The results showed that intrinsic reward significantly affected job satisfaction with count t table (4,564 1699). This shows Ha is rejected and Ho is accepted, which means the extrinsic reward had a significant effect on job satisfaction with the value tcount ttable (3.213 1699). This shows that Ha is rejected and Ho is accepted. It can be said that there is a partial influence between intrinsic reward and extrinsic reward on job satisfaction by looking at the results of the coefficient of determination (r square) of 0.965, which means that the intrinsic reward and extrinsic reward variables can increase job satisfaction by 96.5% and 3.5% are variables residual (residual) which are influenced by other variables.